BENTUK DAN FUNGSI KOMUNIKASI TULIS PADA PAPAN NAMA DILINGKUNGAN KAMPUS - SAHAYU, WENING (Jurnal Penelitian Humaniora, 2015)
Abstract This study aims to describe (1) the forms of text used on the name board in campus; (2) the function of written communication on the nameboard in campus; (3) Dell Hyme's component of written communication on the nameboard in campus. The data of this study are written text on the nameboard in campus. And the analysis method is "˜ Simak' method and "˜Padan' method pragmatic. Result of this study are: (1) its message conveyedto community in campus can be carried out through written communication on the name board. The form of the written communication can be word, p hrase and sentence;(2)the functions of written communication on announcement board in campus is giving information and prohibition; (3) from the analysis based on Hyme's ethnography of communication one important thing is that the language used in written communication on the name board is included into formal language. Keywords: name board language